2021
DOI: 10.1387/ijdb.200072jf
|View full text |Cite
|
Sign up to set email alerts
|

Stress and sex determination in fish: from brain to gonads

Abstract: Fish present remarkable malleability regarding gonadal sex fate. This phenotypic plasticity enables an organism to adapt changes in the environment by responding with different phenotypes. The gonad and the brain present this extraordinary plasticity. These organs are involved in the response to environmental stressors to direct the gonadal fate, inducing sex change or sex reversal in hermaphroditic and gonochoristic fish, respectively. The presence of such molecular and endocrine plasticity gives this group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 96 publications
0
16
0
Order By: Relevance
“…Proposed alternative mechanisms (none of which are mutually exclusive) are the cellular calcium and redox regulation (Castelli et al, 2020;Mukai et al, 2022), epigenetic processes (Shao et al, 2014;Zhang et al, 2022), thyroid hormones (Castañeda-Cortés & Fernandino, 2021;Hayes, 1998;Sun et al, 2016), and the energy limitation hypothesis (Geffroy, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Proposed alternative mechanisms (none of which are mutually exclusive) are the cellular calcium and redox regulation (Castelli et al, 2020;Mukai et al, 2022), epigenetic processes (Shao et al, 2014;Zhang et al, 2022), thyroid hormones (Castañeda-Cortés & Fernandino, 2021;Hayes, 1998;Sun et al, 2016), and the energy limitation hypothesis (Geffroy, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In various vertebrates, dozens of effector pathways and genes involved in sex determination and gonadal development have been identified, including pathways involved in the Sox [ 33 ], Dmrt [ 34 ], Hox [ 35 ], and Wnt [ 36 ] gene families, as well as genes such as Sox9, Sox3, DAX1, AMH, Dmrt1, and Fgf9. The current research has demonstrated that gonadogenesis and development in fish are also co-regulated by these genes [ 37 , 38 ]. We performed a functional analysis of the DEGs, based on the known sequences in the database, and discovered that the DEGs were significantly enriched in the “reproductive process”, “ RNA modification”, “amide biosynthetic process”, “lipid metabolic process”, and “peptide transport processes”.…”
Section: Discussionmentioning
confidence: 99%
“…From an evolutionary perspective, organisms acclimatized themselves to different environments (Kotrschal et al, 1998). As a very important sensory organ with high plasticity (Castañeda‐Cortés & Fernandino, 2021; Dunlap et al, 2019; Noreikiene et al, 2015), the brain plays an important role in fitting organisms to their environments (Hall & Tropepe, 2020; Kotrschal et al, 2017; Schulz‐Mirbach et al, 2016). However, studies on the brain of the Hemiculter leucisculus brain mainly focus on its morphological description (Lu & Li, 1996), but do not explore how the brain changes along the environmental gradients.…”
Section: Introductionmentioning
confidence: 99%